2021
DOI: 10.3390/v13102057
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization and Pathogenicity of H7N7 and H7N9 Avian Influenza Viruses Isolated from South Korea

Abstract: H7 low pathogenic avian influenza viruses (LPAIVs) can mutate into highly pathogenic avian influenza viruses (HPAIVs). In addition to avian species, H7 avian influenza viruses (AIVs) also infect humans. In this study, two AIVs, H7N9 (20X-20) and H7N7 (34X-2), isolated from the feces of wild birds in South Korea in 2021, were genetically analyzed. The HA cleavage site of the two H7 Korean viruses was confirmed to be ELPKGR/GLF, indicating they are LPAIVs. There were no amino acid substitutions at the receptor-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 80 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Studies that reported both prevalence and seroprevalence had a risk of bias, assessed by sorting each result. Prevalence studies that used samples from the entire nation [ 8 , 17 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ] or major migratory bird habitats [ 2 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] determined that the sampling frame was properly chosen, as samples were taken from within the pertinent regions to calculate the prevalence therein. The sampling frame made for the studies whose primary goal was to identify the characteristics of isolated AIVs [ 64 , 65 , 66 , 67 ] was judged to be at a high risk of bias because the isolation rate reported in the studies was constrained to a particular region.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies that reported both prevalence and seroprevalence had a risk of bias, assessed by sorting each result. Prevalence studies that used samples from the entire nation [ 8 , 17 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ] or major migratory bird habitats [ 2 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] determined that the sampling frame was properly chosen, as samples were taken from within the pertinent regions to calculate the prevalence therein. The sampling frame made for the studies whose primary goal was to identify the characteristics of isolated AIVs [ 64 , 65 , 66 , 67 ] was judged to be at a high risk of bias because the isolation rate reported in the studies was constrained to a particular region.…”
Section: Resultsmentioning
confidence: 99%
“…Seven primary studies that evaluated the prevalence of AIVs were judged to have a low bias in the sampling method, owing to proper capture methods from randomized wild birds [ 2 , 41 , 42 , 43 , 48 , 50 , 57 ]. All studies, except for two [ 59 , 66 ] that did not describe the isolation method in detail, recorded the condition of the samples by examining them with the proper techniques, such as RT-PCR [ 2 , 8 , 17 , 41 , 42 , 43 , 44 , 48 , 49 , 50 , 51 , 52 , 54 , 55 , 56 , 58 , 60 , 61 , 62 , 65 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], rRT-PCR [ 53 , 63 , 64 , 75 , 76 ], or HA tests [ 41 , 42 , 46 , 47 , 57 , 77 ]. All investigations, except for 12 studies [ 8 , 46 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations